APLIKASI PENAMPIL WARNA PELITUR PRODUK FURNITURE DENGAN AUGMENTED REALITY DI TOKO UD. CIPTA KARYA DENGAN ALGORITMA FAST CORNER DETECTION - Riyan Priyambodo Pradana; Arin Yuli Astuti; Ismail Abdulrazzaq Zulkarnain (Universitas Muhammadiyah Ponorogo, 2021)
The furniture industry is very much sought after by consumers because of its many uses and plays an important role in household life and daily activities. In its development, consumers want results that are as expected, therefore augmented reality is created which can be scanned on the camera so that objects appear in 3D and consumers can get a picture and producers can provide additional explanations. This augmented reality android application was developed using Unity 3D software and an engine from Vuforia by applying the fast corner detection algorithm method. The results of the target image detection test are influenced by several factors such as light intensity, distance and angle of detection, these affect the marker detection process. When the light intensity is low, the marker detection process is getting more difficult. The farthest distance that can be achieved to detect markers is around 70cm. The test results of the marker's point of view can be detected with a slope angle of +45o. And based on the test results on the ar system of this application, the accuracy level of marker detection is very good